FORMULATION AND EVALUATION OF TWO CELASTROL NANOEMULSIONS PREPARED FROM TWO OILS: ISOPROPYL MYRISTATE AND VIRGIN COCONUT OIL - ABDULLAH, NUR ALAM; JUFRI, MAHDI; MUN’IM, ABDUL; SAPUTRI, FADLINA CHANY (International Journal of Applied Pharmaceutics, 2022)
Objective: Celastrol, which is classified as BCS 4, needs to be developed into a nanoemulsion formula for a stable and good formulation. The aim of the study was to determine the in vitro penetration ability and adsorption efficiency (EE) between two different base oils, namely Isopropyl myristate (IPM) and virgin coconut. oil (VCO). Methods: Two celastrol nanoemulsion formulas were prepared by high energy method using High share homogenizer (HSH) at 15,000 rpm for 15 min, using different oil-based components, F1 IPM and F2 VCO. Particle size, polydispersity index (PDI), D90, zeta potential, and morphology of nanoemulsions was evaluated. In vitro studies by Franz diffusion cell test method determined the difference. Results: The results showed that celastrol can be formulated well with a ternary ratio of 5:45:50 for IPM and 20:30:50 for VCO. The absorption efficiency test for celestrol levels was 96.49%±2.72 for IPM and 76.53%±1.19 for VCO. The mean particle size, PDI, and zeta potential were 70.81±0.20 nm, 0.1±0.03, and 50.2±0.60 mV, for VCO and 186.23±3, respectively. 12 nm, 0.2±0.07, and 45.5±1.10 mV for HDI. Spherical morphology<200 nm. Franz diffusion in vitro at 20 and 24 h, celastrol is well penetrated at levels of 2.4 g/ml gram and 2.5 g/ml for HDI and at 2.0 g/ml gram and 2.4 g/ml, respectively. ml/gram for VCO. Conclusion: Celastrol was successfully developed into nanoemulsions using IPM or VCO, particle size<200 nm, and stable spherical shape.